Positive Behavioral Strategies for Students with EBD and Needed Supports for Teachers and Paraprofessionals - Lukowiak, Twila (Journal of the American Academy of Special Education Professionals, 2010)
This article reveals the findings of a multiple case study that demonstrates the behavioral strategies implemented by select elementary personnel that work daily with students with emotional and behavioral disorders (EBD). The personnel who took part in this study were special education behavioral teachers, special education behavioral paraprofessionals, and general education teachers. Each person utilized varying behavioral strategies to teach students with EBD. This study also reveals the teachers and paraprofessional’ perceptions concerning which of these strategies were the most beneficial in producing improvements in students with EBD. Finally, the study discloses the additional supports that teachers and paraprofessionals need in order to more effectively teach their students.